Pembahasaan Pada Signboard di Pura Dalem Ped Nusa Penida, Klungkung, Bali - Nyoman Sujaya; Anak Agung Inten Mayuni; Made Detrichyeni Winaya (Postgraduated Community Service Journal, 2023)
This article talks about wording the rules in signboard installed in Dalem Ped Temple Nusa Penida Bali when doing social work. It focuses on translating the rules from Balinese into Indonesian and English. Besides, the social work also gave mentoring and lectures about communicative English functions to the staff of Pura Dalem Ped temple. Using the descriptive analysis and observation and interview techniques it can be explained that translation involves culture, context and situation. To have a good translation a translator should be good at both source and target language text. Translation deals with expressing the source language message into target language text. It is the meaning that should be transferred or informed. Since every language has its own form and meaning, there must be shift in everyone’s translation. There is no formal correspondence in translating the source language text into the target language. Dealing with the translation of the languages displayed in the signboard, it could be explained that the translation of the text in the signboard was accurate, readable and acceptable.